The Transformation of Sharia Values through Gurēe Communication in Shaping the Character of Santri at Dayah MUDI Masjid Raya Samalanga - Abrar Azizi, Muhammad; Abdul Kadir, Muntasir; Abdullah, Amiruddin; Arahman, Zulfikar; Ibrahim, Munawir (El-Usrah: Jurnal Hukum Keluarga, 2025)
The transformation of sharia values through faith-based education plays a crucial role in shaping the character of the younger generation. Dayah, as a traditional Islamic educational institution, has a significant role in internalizing these values through the communication between gurēe and students. This study aims to identify the role of interpersonal communication by gurēe in shaping the Islamic character of students at Dayah MUDI Masjid Raya Samalanga. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with gurēe and students, direct observations of daily activities, and document analysis, including curriculum and teaching materials. Thematic analysis was used to identify key patterns in gurēe communication supporting the transformation of sharia values. The findings reveal that interpersonal communication by gurēe plays a central role in transforming sharia values. This process involves not only formal teaching but also personal approaches, open dialogues, and exemplary behavior by gurēe. This approach creates a supportive educational environment where students feel encouraged to internalize sharia values into their attitudes and behaviors. This study contributes to the Islamic education literature by emphasizing the importance of interpersonal communication as an effective strategy for building a sharia-based character in the younger generation.